2014
DOI: 10.4103/1463-1741.127858
|View full text |Cite
|
Sign up to set email alerts
|

Development of a traffic noise prediction model for an urban environment

Abstract: The objective of this study is to develop a traffic noise model under diverse traffic conditions in metropolitan cities. The model has been developed to calculate equivalent traffic noise based on four input variables i.e. equivalent traffic flow (Q e ), equivalent vehicle speed (S e ) and distance (d) and honking (h). The traffic data is collected and statistically analyzed in three different cases for 15-min during morning and evening rush hours. Case I represents congested traffic where equivalent vehicle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…But commonly accessible professional calculation programmes do not have such a function. Another problem seems to be the statistics base applied for validation of calculation programmes, which is also highlighted by the authors of [5,21]. Probably it does not fully cover the real randomness of traffic.…”
Section: Discussionmentioning
confidence: 99%
“…But commonly accessible professional calculation programmes do not have such a function. Another problem seems to be the statistics base applied for validation of calculation programmes, which is also highlighted by the authors of [5,21]. Probably it does not fully cover the real randomness of traffic.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic noise was recorded manually using sound level meter with accuracy of ±0.1% [19]. Vehicle volume, average speed and honking are measured for the total duration of 15-minute with one minute intervals during morning (10:00 to 11:00) and evening (18:00 to 19:00) peak traffic hours respectively at each selected location (Table 1) [5]. The vehicle volume has been classified into four categories, i.e.…”
Section: Data Acquistionmentioning
confidence: 99%
“…In the model 3 "gbellmf" membership functions were selected for each input. The numerical ranges were used for Q E (45.35-373.9), for S E (23.91-49.28), for honking (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) respectively. Membership functions of inputs are displayed in Fig.…”
Section: Development Of Anfis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been no standard traffic noise model followed in Indian conditions, although many studies have been reported in recent years in various parts of the country [10][11][12][13][14][15] . The Central Pollution Control Board (CPCB), Delhi has taken many initiatives and carried out numerous studies for monitoring the ambient noise levels at hot spots in Delhi and implementation of suitable measures to be adopted for noise mitigation.…”
Section: Introductionmentioning
confidence: 99%